Evaluasi Kondisi Perkerasan Lentur Jalan Magelang Km 7 – 9 Menggunakan Metode PCI dan Bina Marga 2024 dengan Pendekatan Mekanistik Empirik - Wangga Ardiputra; Miftahul Fauziah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The Magelang KM 7–9 roadway connecting Yogyakarta and Magelang is an arterial road with high traffic volumes, making it susceptible to pavement deterioration and performance decline. Increases in traffic loading and environmental factors have led to various surface distresses that can affect user comfort and safety. Therefore, a comprehensive evaluation of pavement condition and performance is necessary as a basis for determining appropriate treatment measures. This study aims to evaluate the functional condition and structural performance of flexible pavements using the Pavement Condition Index (PCI) method and the 2024 Bina Marga method based on a mechanistic–empirical approach. The PCI method was applied to identify and assess pavement surface distress in terms of type, severity, and extent. Meanwhile, the 2024 Bina Marga guideline issued by the Ministry of Public Works and Public Housing was used to analyze pavement structural capacity, remaining service life, and overlay thickness requirements. The results indicate that pavement condition is classified as good, with PCI values of 64.9 in the direction toward Magelang and 64.25 in the direction toward Yogyakarta. The maximum strain–stress response occurred at a depth of 19.998 cm. The estimated allowable repetition of loads for rutting damage is 13,465,609 ESAL, for fatigue cracking 183,344,713 ESAL, and for deformation 4,371,054 ESAL. Predicted remaining life due to deformation under equivalent standard loading in the first year is 56.88% and is exhausted by year 3. For rutting, remaining life in the first year is 86.00% and is exhausted by year 6. For fatigue cracking, remaining life in the first year is 98.97% and remains 80.46% at year 10. Because the cumulative ESA4 exceeds 10,000,000, the AASHTO 1993 equation was used, producing a required overlay thickness of 6 cm at station 4500 in the direction toward Yogyakarta, with a subgrade CBR value of 4.7%.